Simultaneous determination of pyrrolizidine and tropane alkaloids in honey by liquid chromatography–mass spectrometry - Kowalczyk Ewelina; Kwiatek Krzysztof (Journal of Veterinary Research, 2022)
Pyrrolizidine alkaloids (PAs) and tropane alkaloids (TAs) are natural contaminants of honey and respectively hepatoxic and neurotoxic compounds. Because honey is a popular constituent of the human diet, it is relevant to warrant the safety of the product. For that reason, a method for simultaneous determination of PAs and TAs in honey based on liquid chromatography– mass spectrometry was developed.